Penghematan Energi Pada Sistim Pendingin Bangunan Hotel “The Dharmawangsa - Wishnuwardhana Jam; Koswara Koswara; Nofirman Nofirma (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract : Conservation of natural resources, one of which is electrical energy, is mostly generated from limited natural resources such as coal, petroleum, and natural gas. Electrical energy is crucial in the natural hospitality/ tourism industry, where air conditioning (AC) equipment consumes a significant amount of electrical energy, typically accounting for around 60% of the electricity usage. The purpose of this research is to analyze the consumption of electrical energy related to the operational efficiency of a hotel building. Energy auditing is the technique used to calculate the energy consumption and determine methods to control it in order to achieve energy savings. The activity involves determining the “Energy Efficiency Ratio” based on standards applied in Indonesia. By implementing electrical energy conservation measures, there can be economic benefits as well. The more efficient the energy usage, the lower the costs incurred to meet electricity needs. Keywords : Conservation Energy, Cold Storage